Risk Factors for Recurrent Helicobacter cinaedi Bacteremia and the Efficacy of Selective Digestive Decontamination With Kanamycin to Prevent Recurrence. (15th February 2018) - Araoka, Hideki; Baba, Masaru; Okada, Chikako; Kimura, Muneyoshi; Sato, Tomoaki; Yatomi, Yutaka; Moriya, Kyoji; Yoneyama, Akiko
Abstract : The 100-day cumulative incidence of recurrent Helicobacter cinaedi bacteremia was 18.7%. Anticancer chemotherapy and systemic steroids were independent risk factors for recurrent bacteremia. Selective digestive decontamination is a potential strategy for reducing the rate of recurrent bacteremia. Abstract: Background: Previous studies suggest that Helicobacter cinaedi can cause recurrent bacteremia. In this study, we elucidated the risk factors for recurrent H. cinaedi bacteremia and explored the efficacy of selective digestive decontamination (SDD) as a preventive measure. Methods: We retrospectively reviewed the medical records of patients with H. cinaedi bacteremia between March 2009 and December 2016 at 2 Japanese hospitals. Results: We identified 168 patients with H. cinaedi bacteremia. Bacteremia recurred in 34 patients. The 100-day cumulative incidence rate of recurrent bacteremia was 18.7%. In univariate analysis of factors associated with recurrent bacteremia, anticancer chemotherapy (hazard ratio [HR], 3.75; 95% confidence interval [CI], 1.86–7.58; P < .001), systemic steroids (HR, 3.79; 95% CI, 1.70–8.45; P = .0011), and hematological malignancy (HR, 3.18; 95% CI, 1.64–6.19; P < .001) were detected. Multivariate analysis indicated that anticancer chemotherapy (HR, 2.47; 95% CI, 1.19–5.12; P = .015) and systemic steroids (HR, 2.40; 95% CI, 1.03–5.61; P = .044) were the independent risk factors. Of the 168 patients, 47 received SDD. According to Gray's test, SDD might have reduced the rate of recurrence but this was not statistically significant (HR, 0.46; 95% CI, 0.18–1.18; P = .11). However, in a proportional hazard modeling analysis, SDD reduced the rate of recurrence (HR, 0.36; 95% CI, 0.13–1.00; P = .050). Conclusions: The 100-day cumulative incidence of recurrent H. cinaedi bacteremia was 18.7%. Anticancer chemotherapy and systemic steroids were independent risk factors for recurrent bacteremia. SDD is a potential strategy for reducing the recurrence.